What Do We Know About the Macroeconomic Effects of Fiscal Policy? A Brief Survey of the Literature on Fiscal Multipliers. (28th February 2019) - Castelnuovo, Efrem; Lim, Guay
Abstract: This article discusses recent research on the macroeconomic effects of fiscal policy—the theme of the 2018 edition of the Melbourne Institute Macroeconomic Policy Meeting. We review recent research findings on the effects of fiscal multipliers in normal times, during booms/busts, and in the presence of the zero lower bound. Studies on the effects of fiscal policy in open economy settings as well as contributions on the fiscal‐monetary policy mix are also considered. We conclude by outlining a few research avenues that are particularly relevant from a policy standpoint.